PENGARUH EFIKASI DIRI, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL YANG DIMODERASI OLEH BUDAYA KLAN ORGANISASI (Studi Pada Perusahaan House Of Susan Semarang) - Priscilla Angel Susetya, 14.05.51.0067; Fauzan, Mohammad (Students' Journal of Economic and Management, 2018)
The purpose of this study waas to determine the effect of Self Efficacy, Work Discipline, Work Motivation on Organizational Commitment moderated Clan Culture Organization. The population in this study are employees who work there. The sampling in this research same with the population it was sensus. Data collection was done through questionaires. Regresion analysis revealed that Self Efficacy and Work Discipline influence Organizational Commitment. Motivation Work, and Clan Culture Organization uninfluence Organizational Commitment. Clan Culture Organization as moderated variable unmoderated influence of Self efficacy, Work Discipline, Work Motivation on Organizational Commitment.Keywords : Self Efficacy, Work Discipline, Work Motivation, Clan Culture Organization and Organizational Commitment